2019
DOI: 10.1111/ijd.14363
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open, controlled trial of tretinoin 0.05% cream vs. low-dose oral isotretinoin for the treatment of field cancerization

Abstract: A randomized, open, controlled trial of tretinoin 0.05% cream vs. low-dose oral isotretinoin for the treatment of field cancerization Abstract Background Sun exposure may lead to actinic keratoses (AKs), field cancerization, and skin cancer. Effective treatment of AKs and field cancerization is important. Oral and topical retinoids can be used for this purpose. To compare clinical, histological, and immunohistochemical effects of oral and topical retinoid for AKs and field cancerization on face and upper limbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…We suggested that retinoids can be considered as maintenance therapy with the purpose of stabilizing the skin field of cancerization, after a destructive treatment (e.g., cryosurgery). 8 Despite four basal-cell carcinomas detected throughout the study (secondary endpoint), our conclusions do not allow recommendations regarding the specific chemoprevention of skin cancer. 8 We also followed 34 excluded patients who only used sunscreen after cryosurgery.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We suggested that retinoids can be considered as maintenance therapy with the purpose of stabilizing the skin field of cancerization, after a destructive treatment (e.g., cryosurgery). 8 Despite four basal-cell carcinomas detected throughout the study (secondary endpoint), our conclusions do not allow recommendations regarding the specific chemoprevention of skin cancer. 8 We also followed 34 excluded patients who only used sunscreen after cryosurgery.…”
mentioning
confidence: 67%
“…8 Despite four basal-cell carcinomas detected throughout the study (secondary endpoint), our conclusions do not allow recommendations regarding the specific chemoprevention of skin cancer. 8 We also followed 34 excluded patients who only used sunscreen after cryosurgery. They disclosed an inferior performance (À27%) to both retinoid groups (À40%) in AK count reduction, providing evidence that retinoids can benefit the treatment of field cancerization.…”
mentioning
confidence: 67%
“…Retinoids have propable chemopreventive properties through its effect on mutations of p53 protein, together with normalization of epithelial cellular differentiation and deactivation of the apoptotic pathways. Researchers suggested isotretinoin in a dose of 10 mg/day can be a safe alternative for treatment of the precancerous actinic keratosis (Ianhez, Pinto, Bagatin, & Miot, ). Furthermore, maintenance therapy with retinoids, including low‐dose isotretinoin, is suggested for stabilization of the skin field of cancerization (Ianhez, Pinto, Miot, & Bagatin, ).…”
Section: Indications Of Low‐dose Isotretinoin In Dermatologymentioning
confidence: 99%
“…Their data demonstrate no difference in the number of AKs at the end of the trial between the two groups . They conclude that both treatments were effective for field cancerization, a conclusion unrelated to the random assignment of treatments.…”
mentioning
confidence: 98%
“…It is with interest that we read the paper by Ianhez et al . on retinoid use in patients with field cancerization . The authors are reporting a randomized clinical trial with 61 participants that compares the efficacy of 0.05% tretinoin cream vs. oral isotretinoin for the treatment of actinic keratoses (AKs).…”
mentioning
confidence: 99%